A processual method, the method helping to manage the quality of transport services - Pankov, Aleksandr; Petuhov, Igor; Shestakov, Vladimir (Transport, 2005)
Transportation organization is inspected as three ground processes and each of these processes has dynamic indices. The connection of undynamics between these indices is the foundation for managing, the acception of managment decision and for a big number of other actions. There are some results of the aprobation of this method.First Published Online: 27 Oct 2010